Characterizing chain‐end structures formed during initiation reactions of radical polymerization for MMA‐St‐BA terpolymer using pyrolysis‐gas chromatography/atmospheric pressure chemical ionization high‐resolution time‐of‐flight mass spectrometry. (11th February 2020) - Harata, Kenji; Kitagawa, Shinya; Iiguni, Yoshinori; Ohtani, Hajime; Ezaki, Tatsuya
Abstract : Rationale: Analyzing polymer end groups using pyrolysis (Py) gas chromatography/mass spectrometry (GC/MS) in multi‐component polymer samples is not an easy task because of the insufficient sensitivity, selectivity, and mass resolution of conventional Py‐GC/MS systems. Methods: A new Py‐GC/MS system using an atmospheric pressure chemical ionization (APCI) source combined with high‐resolution time‐of‐flight mass spectrometry (TOFMS) was used for end‐group analysis of a methyl methacrylate (MMA)‐styrene (St)‐butyl acrylate (BA) terpolymer (P (MMA‐St‐BA)), which was radically polymerized using 2, 2′‐azobis(2‐methylbutyronitrile) (AMBN) as an initiator. Results: Five possible pyrolyzates, comprising an AMBN fragment and a monomer unit, formed during the initiation reactions from one of the three types of end groups, were selectively detected and exclusively identified in their respective extracted ion chromatograms for molecule‐related ions, such as M + and [M + H] +, with a narrow mass window of ±2 milli m/z units. Conclusions: It was demonstrated that Py‐APCI‐TOFMS is a powerful technique to characterize in detail the complex end groups in multi‐component polymer samples, because of the soft ionization nature of APCI and the high mass resolution of TOFMS.